Glycerol is not an inhibitor of mitochondrial citrate oxidation by Aspergillus niger - ArisanAtac, I; Kubicek, CP (MICROBIOLOGY SOC, 1996)
We have re-assessed the hypothesis that an accumulation of intracellular glycerol triggers the accumulation of citric acid by Aspergillus niger by inhibiting the activity of the mitochondrial NADP-dependent isocitrate dehydrogenase isoenzyme. To this end, we have incubated mycelia of A. niger with 0 . 5 M glycerol, which resulted in a maximal intracellular glycerol pool level of 0 . 92 M, comparable to that determined during the early phase of citrate accumulation. This addition affected neither the uptake of [1,5-C-14]citrate from the medium nor the rate of the subsequent release of (CO2)-C-14 by the mycelia, indicating no effect on citrate oxidation. Mitochondria isolated from mycelia previously loaded with 0 . 5 M glycerol contained 8% of the total mycelial glycerol. They released (CO2)-C-14 from exogenously added [1,5-C-14]citrate at the same rate as mitochondria isolated from mycelia not loaded with 0 . 5 M glycerol. The addition of glycerol had no effect on the activity of the purified NADP-specific isocitrate dehydrogenase, but appeared to inhibit the activity in crude cell-free extracts of A. niger. We conclude that the intracellular accumulation of glycerol does not affect the rate of mitochondrial citrate oxidation and is therefore, in contrast to previous claims, not a trigger of citrate accumulation.
Keywords: Aspergillus niger; citric acid accumulation; glycerol; isocitrate dehydrogenase; CITRIC-ACID ACCUMULATION; FERMENTATION; MANGANESE; BINDING; Microbiology